Solvent-Free Henry and Michael Reactions with Nitroalkanes Promoted by Potassium Carbonate as a Versatile Heterogeneous Catalyst - Giovanna Bosica; Kurt Polidano (Journal of Chemistry)
The use of a simple weak inorganic base such as potassium carbonate facilitated the formation of carbon-carbon bonds through both the Henry and the Michael reactions with nitrocompounds. The application of this catalyst under environmentally friendly solventless heterogeneous conditions gave satisfactory to good yields of β-nitroalcohols, involving aliphatic and aromatic starting materials, as well as high to excellent yields in the formation of Michael adducts using several different Michael acceptors and nitroalkanes.